NITROGEN FERTILIZATION IN IMPLEMENTATION OF Urochloa Brizantha cv. Xaraés IN BRAZILIAN SAVANNA - Part 1 - Santini, J. M. K.; Perin, A.; Coaguila, D. N.; Valderrama, M.; Dupas, E.; dos Santos, C. G.; Silva, V. M.; Buzetti, S. (Revista Brasileira de Engenharia de Biossistemas, 2016)
Fertilization has provided great advances in productivity and quality of pastures, and among nutrients, the nitrogen (N) is noteworthy for its large extraction and increased productivity of Poaceae, however, after its application to the soil is influenced by the site and can be lost when misdirected. To minimize this problem, an alternative promising is the use of enhanced efficiency fertilizers, seeking to reduce these losses and provide increased productivity. Thus, we evaluated the effect of sources and doses of N in the implementation of Urochloa brizantha cv. Xaraés (grass-xaraés) on productivity and bromatologic values in cultivation in Cerrado conditions. The experiment was conducted in the experimental area in Rio Verde - GO, Brazil, distributed in a randomized block design with four replications, in a factorial arrangement of 3x4. The first factor was three sources of N (conventional urea, increased efficiency of urea and ammonium nitrate); the second factor was four nitrogen doses (0, 20, 40 and 80 kg N ha-1 clip-1). The use of conventional urea is the best alternative to the culture of grass-xaraés. The recommended dose of nitrogen is 80 kg ha-1 by clipping, for increasing the production of dry mass, and the improvement of the bromatological quality of the grass-xaraés.